Impact of consumer ethnocentrism and country of origin image on consumer beliefs and attitudes to purchase products made in Indonesia and Malaysia : Case study of West Kalimantan, Indonesia and Sarawak, Malaysia - Heriyadi, Kusyarnadi (unimas, 2016)
The globalization of business and marketing has provided consumers, all over the world, with many options to purchase products. The situation is more complex especially in the area where the regions as part of the share lands and boundaries between countries like Sarawak Malaysia and Kalimantan Barat-Indonesia. In the international marketing literature’s theories, tremendous attention has been given to examining the extent to which the image of the country-of-origin of the product and consumer ethnocentrism influences consumer perception and product evaluation. But still, the research about country image and consumer ethnocentrism that is conducted in the border area is very rare and limited. This study investigates the attitudes of the consumers and how they evaluate the products from both countries (Indonesia-Malaysia). The objectives of this thesis is to justify the relationship among variables (consumer ethnocentrism, country of origin image, Beliefs, and Attitudes) based on the framework of the proposed model. Moreover, this thesis explores the mediating role of COI and Beliefs on the relationship of consumer ethnocentrism with attitudes and relationship between COI and attitudes. These relationships will each be assessed at the level of product involvement (High-Low), cross-national characteristics (Indonesia-Malaysia), and the cross-culture of the ethnic groups (Malay-Chinese Malaysian Chinese and Malay Indonesian). The structural equation modeling (SEM) approach is employed in this study. The proposed reach a better goodness of fit. Hence, the proposed model can be used to explain the influence of Consumer Ethnocentrism and Country of origin image on beliefs and attitudes for both Car and Noodle. All hypothesized relationship and mediating effect are supported.